2013
DOI: 10.1134/s1811238213070060
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of lipid membranes: Methodology and achievements

Abstract: Rapid development of computer power during the last decade has made molecular simulations of lipid bilayers feasible for many research groups, which, together with the growing general interest in investi gations of these very important biological systems has lead to tremendous increase of the number of research on the computational modeling of lipid bilayers. In this review, we give account of the recent progress in com puter simulations of lipid bilayers covering mainly the period of the last 7 years, and cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 321 publications
0
16
0
Order By: Relevance
“…The second position is often competitively occupied by PUFAs and/or SFAs. In this case, we should mention the relationship between the results of this work and theoretical studies of the properties of FA chains (the shape and flexibility of FA chains) in an unperturbed state, obtained by computer simulation with the Monte Carlo method [63,64,73,74]. In particular, it was found that FA chains (16:0, 18:1(n-9)cis, 18:2(n-6)cis, 18:3(n-3)cis, 20:3(n-6)cis, 20:4(n-6) cis, 20:5(n-3)cis, 22:5(n-3)cis, 22:6(n-3)cis), i.e., key FAs for the studied fish, have equal longitudinal sizes due to which molecular substitutions, manipulations, and complementarity (in the properties) of these FAs in the PL structure achieve constant thickness of the membrane hydrocarbon layer and adjust its fluidity, which ensures the functionality of the lipid bilayer under changing environmental factors.…”
Section: Discussionmentioning
confidence: 91%
“…The second position is often competitively occupied by PUFAs and/or SFAs. In this case, we should mention the relationship between the results of this work and theoretical studies of the properties of FA chains (the shape and flexibility of FA chains) in an unperturbed state, obtained by computer simulation with the Monte Carlo method [63,64,73,74]. In particular, it was found that FA chains (16:0, 18:1(n-9)cis, 18:2(n-6)cis, 18:3(n-3)cis, 20:3(n-6)cis, 20:4(n-6) cis, 20:5(n-3)cis, 22:5(n-3)cis, 22:6(n-3)cis), i.e., key FAs for the studied fish, have equal longitudinal sizes due to which molecular substitutions, manipulations, and complementarity (in the properties) of these FAs in the PL structure achieve constant thickness of the membrane hydrocarbon layer and adjust its fluidity, which ensures the functionality of the lipid bilayer under changing environmental factors.…”
Section: Discussionmentioning
confidence: 91%
“…We chose these particular models because the lipid model has been validated also at low hydration with the water model, 37 verified parameters are available for both saturated and unsaturated lipids, 37 and force field consistent parameters for cyclohexane exist. 38 Furthermore, the accuracy of the lipid model compares favourably to other commonly used lipid force fields in a recent review, 1 or is among the best performing in several others 2,4 with specifically the deuterium order parameters most accurately reproduced. 4 In total, the force field is a very good candidate for good performance in describing the PC/cyclohexane system.…”
Section: Methodsmentioning
confidence: 99%
“…CHARMM36 force field performs very well in describing all the studied components individually or in aqueous environment, 37,38 and is currently one of the highest regarded lipid force fields, with good accuracy in water environment. [1][2][3][4] However, the FIG. 7.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The simulations provide atomically detailed pictures of membrane statics and dynamics, and of the interactions of the membrane with other molecules. Of interest to the present article are permeability and insertion of medium size molecules into bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest to the present article are permeability and insertion of medium size molecules into bilayers. 12,13,16,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Passive transport (without involving cellular machinery such as pumps) is an important biological process in cellular biology. At the least, living system must adapt to minimize this type of process for invading or not losing materials.…”
Section: Introductionmentioning
confidence: 99%